2012
DOI: 10.1177/0020764012448781
|View full text |Cite
|
Sign up to set email alerts
|

Changing attitude to mental illness among community mental health volunteers in south-western Nigeria

Abstract: Attitudes of community volunteers towards persons with mental illness improve with educational programmes. This may lead to improved treatment and care of individuals who are mentally ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Literature on the relation of caregiver’s gender with attitude towards people with mental illness is inconsistent. Studies from India and Nigeria reported that female sex was not a predictor of poor attitude towards PWMI [ 30 , 31 ], while findings of a study from England and Qatar claimed the other way round [ 32 , 33 ]. This can be attributed to the gender roles as gender is a complex construct determined by culturally set conventions, practices and behaviours [ 34 ] and differs between nations.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the relation of caregiver’s gender with attitude towards people with mental illness is inconsistent. Studies from India and Nigeria reported that female sex was not a predictor of poor attitude towards PWMI [ 30 , 31 ], while findings of a study from England and Qatar claimed the other way round [ 32 , 33 ]. This can be attributed to the gender roles as gender is a complex construct determined by culturally set conventions, practices and behaviours [ 34 ] and differs between nations.…”
Section: Discussionmentioning
confidence: 99%
“…When one has higher levels of education, they tend to use multiple resources to understand complicated information about mental illness (Kidane, 2014 21 knowledge on mental illness, which is associated with benevolent attitude towards mental illness (Aghanwa, 2004). For example, community volunteer workers who participated in educational programme raising awareness on mental illness significantly improved their attitudes towards mental illness (Abayomi, Adelufosi, & Olajide, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This is because policy makers can be a contributing effect in combating stigma by investing in such measures (Arthur, Hickling, Robertson-Hickling, Haynes-Robinson, Abel, & Whitley, 2010). The effect of such campaign or intervention definitely improves one's' attitudes towards those who are mentally ill (Abayomi et al, 2013). However, knowledge can be a double-edged sword as information about mental illness promotes social distance.…”
Section: Resultsmentioning
confidence: 99%
“…This being said, applicability in other contexts remains uncertain without replication in other regions. This is particularly relevant as befriending appears to be globally applied; a systematic review found schemes in Germany, the United Kingdom, and United States (Hallett et al, 2012) with other schemes researched in Nigeria (Abayomi, Adelufosi, & Olajide, 2013).…”
Section: Discussionmentioning
confidence: 99%